Polis e virtude em Aristóteles - Pereira, Reinaldo Sampaio [UNESP] (My University, 2010)
We will examine in this article to what extent the research about virtue in the Nicomachean Ethics aims enable happiness and how the happiness requires the common life in the polis. We will look for examine, through the relationship between virtue, someone’s happiness, polis and good of the polis, as how good organization of the polis is presented somehow as a necessary condition, but not enough, for the virtuous life and consequently for the happy life, the men’s last ending as evidenced by EN from its opening chapters.

Examinaremos, neste artigo, em que medida a investigação acerca da virtude na Ética a Nicômaco tem como propósito possibilitar a felicidade e como essa pressupõe a vida coletiva na pólis. Procuraremos examinar, através da relação entre a virtude, a felicidade do indivíduo, a pólis e o bem da pólis, como a boa organização da pólis apresenta-se, de certo modo, como condição necessária, ainda que não suficiente, para a vida virtuosa do indivíduo e, conseqüentemente, para a vida feliz, fim último próprio ao homem, como atesta a EN a partir dos seus capítulos iniciais.